A gateway for nature lovers - Evans, J (Waratah Wynyard Council, 2009)
Background The Tarkine is located in Tasmanias North West, and loosely defined as an area of wilderness bound by the Arthur river to the north, Pieman River to the south, the Murchison Highway to the east and the Southern Ocean to the west. This area of 475,000 Ha has been the subject of much environmental controversy and debate since the 1990s. Today the Tarkine is recognised internationally for containing the largest contiguous tract of cool temperate rainforest in the Southern Hemisphere and the home of more than 50 threatened and endangered flora and fauna species. The Tarkine holds significant natural and cultural values and has been placed on the National Heritage list for consideration. The tourism value of the Tarkine has been increasingly recognised over the last three years by all levels of government. The State government and the Cradle Coast Authority have developed Tarkine related tourism projects and tourism development strategies for the Tarkine. The sustainable tourism development potential of the Tarkine has been estimated as being significant and may contribute to repositioning Tasmania as a premier nature based destination. The Waratah Wynyard Council has played an active role in the shaping the sustainable tourism policy direction of the Tarkine through its interest in the development of Corinna and Waratah as entry points into the Tarkine and participation on the Tarkine Discussion Group. The Waratah Wynyard Council has been instrumental in delivering two recent projects to Waratah; the Stamper Mill and the redevelopment of the Athenaeum Hall. Both these projects provide meaningful interpretation of Waratah and the Tarkine delivering on the key flagship attributes of the Tarkine brand. The Waratah Wynyard Council wishes to capture the market potential of the Tarkine concentrating on providing authentic nature based experiences in and around Waratah. This project proposes five experiences aimed at meeting the demand and expectations of the nature based market as identified by the Cradle Coast Authoritys Tarkine Tourism Development Strategy October 2008. The projects proposed have been endorsed by several organisations and groups as being priority areas for development including the Cradle Coast Authority, Sport & Recreation Tasmania and the Tarkine National Coalition. The projects include a range of short, half day and multi day walks as well as mountain bike experiences all supported by various quality interpretation and day use facilities.